Potential impact of a pilot training program on smoking cessation intervention for tuberculosis DOTS providers in Malaysia - Awaisu, Ahmed; Nik Mohamed, Mohamad Haniki; Mohamad Noordin, Noorliza; Abd. Aziz, Noorizan; Syed Sulaiman, Syed Azhar; Muttalif, Abdul Razak; Ahmad Mahayiddin, Aziah (Springer, 2010)
Background The association between tuberculosis (TB)and tobacco smoking is becoming increasingly important. Smoking cessation may yield substantial positive effects on TB treatment outcomes, relapse, and future lung disease. Thus, TB directly observed therapy, short-course (TB DOTS) providers are uniquely positioned to intervene with those TB patients who are smokers. Unfortunately, most health care professionals are inadequately trained to provide such service.